Revisiting the taxonomy and nomenclature of Phyla , a small genus of Verbenaceae - Cardoso, Pedro Henrique (2025)
Phyla is unique within Verbenaceae due to the presence of malpighiaceous hairs. Its taxonomy has long been marked by difficulties in defining species boundaries. The most recent revision of the genus recognized five species and three varieties. In this study, however, we recognize only two species and no varieties: P. betulifolia, restricted to the Americas, and P. nodiflora, which has a broad distribution across all continents except Antarctica. The former has leaves distinctly petiolate, spikes 1–3 per leaf axil, short peduncles that do not surpass the leaves, and corollas with inconspicuous tubes and lobes. The latter, in contrast, displays sessile or short-petiolate leaves, solitary spikes, long peduncles that often exceed the length of the leaves, and corollas with more prominent tubes and lobes. We provide updated descriptions, photographs, taxonomic notes for each species, and an identification key. Additionally, we present lectotypifications for six taxa, Lippia caespitosa, L. filiformis, L. nodiflora var. pusilla, L. nodiflora var. suborbicularis, L. strigulosa and Verbena sarmentosa, and one neotype for L. aegyptiaca, all of which are considered synonyms of P. nodiflora.